Synthesis and physicochemical characterization of photo crosslinked hydrogels of alginate/gelatin and a-tocopherol nanocapsules for their potential use as biomaterials - Palacios Santos, José Ernesto (2019)
In recent years, great advances have been made in the development of biomaterials for wound healing and tissue regeneration, so they can cover the necessary requirements to be ideal treatments for wounds of difficult healing. Current treatments are materials focused on the protection, absorption of wound exudate and wound healing, however, there are different types of wounds which due to the complexity of healing of the damage tissue, diseases such as diabetes and arterial hypertension or the type of accident that caused them, such as burns or necrosis, the regeneration of the new tissue is more complicated. Therefore, this project proposes the developments of photo crosslinked hydrogel matrices of alginate and gelatin and nanocapsules of polycaprolactone loeaded with atocopherol that have a potential use for a natural regenerative response of the skin by eliminating excessive free radicals. Based on what previously explained the question was raised: Will hydrogels made with biopolymers and loaded with nanoencapsulated a-tocopherol promotes a faster and more effective cell proliferation response? During this investigation, the synthesis of the hydrogels was made by photo crosslink and their physicochemical characteristics were analyzed by gravimetric, spectrophotometric and rheological techniques, while the nanocapsules were formed using nanoprecipitation method and their physicochemical characteristics were also analyzed. In this work, 12 hydrogel formulations were made and analyzed using different crosslinking methods, and it was observed that Photo-crosslinking had no negative effect on its physicochemical characteristics, due to its firmness and its solubility rate are further improved. Also, 13 nanocapsule formulations were made and analyzed employing the nanoprecipitation technique, where it was observed that by modifying the concentrations of the solvents, smaller diameters of the nanocapsules were obtain and using different extraction methods, its encapsulation efficiency and antioxidant activity were improved